A rare presentation of craniopharyngioma: delayed puberty. (29th November 2012) - İnci, Mehmet Fatih; Özkan, Fuat; Bozkurt, Selim; Demir, Caner Feyzi
Abstract : Craniopharyngiomas are the most frequently encountered suprasellar tumours in children. Owing to the slow growth rate of these tumours, they are often quite large before becoming symptomatic. They are more common among children and older adults (55–74 years). Depending upon the direction of growth and tumour size, craniopharyngiomas can affect the hypothalamus, pituitary stalk, optic nerves and chiasm and carotid arteries. Compression of these neural and vascular structures frequently precipitates endocrine disorders, visual loss and an increased intracranial pressure. Hypopituitarism leading to a delayed puberty is a rare presentation of craniopharyngioma. The diagnosis of craniopharyngioma is usually made with the classic radiological imaging features based on CT and MRI.